The Effects of Acute and Chronic Selective Phosphodiesterase 1 Inhibition on Smooth Muscle Cell-Associated Aging Features - Golshiri, Keivan; Ataabadi, Ehsan Ataei; Jüttner, Annika A.; Snyder, Gretchen L.; Davis, Robert E; Lin, Amy; Zhang, Lei; de Vries, René; Garrelds, Ingrid M; Leijten, Frank P. J.; Danser, A. H. Jan; Roks, Anton J. M. (Frontiers in Pharmacology, 2022)
Age-related cardiovascular diseases (CVDs) remain among the leading global causes of death, and vascular smooth muscle cell (VSMC) remodeling plays an essential role in its pathology. Reduced NO-cGMP pathway signaling is a major feature and pathogenic mechanism underlying vasodilator dysfunction. Recently, we identified phosphodiesterase (PDE) 1, an enzyme that hydrolyzes and inactivates the cyclic nucleotides cAMP and cGMP, and thereby provides a potential treatment target for restoring age-related vascular dysfunction due to aging of VSMC. Based on this hypothesis, we here tested the effects of PDE1 inhibition in a model of SMC-specific accelerated aging mice. SMC-KO and their WT littermates received either vehicle or the PDE1 inhibitor lenrispodun for 8 weeks. Vascular function was measured both in vivo (Laser Doppler technique) and ex vivo (organ bath). Moreover, we deployed UV irradiation in cell culture experiments to model accelerated aging in an in vitro situation. SMC-KO mice display a pronounced loss of vasodilator function in the isolated aorta, the cutaneous microvasculature, and mesenteric arteries. Ex vivo, in isolated vascular tissue, we found that PDE1 inhibition with lenrispodun improves vasodilation, while no improvement was observed in isolated aorta taken from mice after chronic treatment in vivo. However, during lenrispodun treatment in vivo, an enhanced microvascular response in association with upregulated cGMP levels was seen. Further, chronic lenrispodun treatment decreased TNF-α and IL-10 plasma levels while the elevated level of IL-6 in SMC-KO mice remained unchanged after treatment. PDE1C and senescence markers, p16 and p21, were increased in both SMC-KO aorta and cultured human VSMC in which DNA was damaged by ultraviolet irradiation. This increase was lowered by chronic lenrispodun. In contrast, lenrispodun increased the level of PDE1A in both situations. In conclusion, we demonstrated that PDE1 inhibition may be therapeutically useful in reversing aspects of age-related VSMC dysfunction by potentiating NO-cGMP signaling, preserving microvascular function, and decreasing senescence. Yet, after chronic treatment, the effects of PDE1 inhibition might be counteracted by the interplay between differential PDE1A and C expression. These results warrant further pharmacodynamic profiling of PDE enzyme regulation during chronic PDE1 inhibitor treatment.